Achieving agricultural sustainability: analyzing the impact of digital financial inclusion on agricultural green total factor productivity - Xu, Ming; Shi, Lidong; Zhao, Jiahui; Zhang, Yili; Lei, Ting; Shen, Yang (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn order to achieve the sustainable development goal set by the United Nations,it is necessary to promote the green transformation and sustainable development of agriculture. In the context of the global economic digital revolution, examining the impact of digital financial inclusion (DFl) on agricultural green total factor productivity (AGTFP) provided a new perspective for DFl to promote agricultural transformation and upgrading.MethodsBased on balanced panel data for 30 provinces in China from 2011 to 2022, the study used the slack-based measure (SBM) and global malmquist-luenberger (GML) index to measure AGTFP. Then the entropy method was used to measure the basic condition of digital logistics. Finally, causal relationship and potential mechanism of DFI on AGTFP were verified by means of bidirectional fixed effect and two-stage least square method.ResultsOur findings are as follows: firstly, DFl significantly increases AGTFP. This conclusion is still valid after a series of robustness tests and endogeneity control. Secondly, land transfer and digital logistics play positive mediating roles in the relationship between DFl and AGTFP. Thirdly, DFl has a higher impact on AGTFP in main grain-producing areas and the production-marketing balanced areas.DiscussionThis research provides not only theoretical and empirical support for optimizing China’s digital inclusive financial service system and promoting the green development of agriculture but also an important reference for the agricultural development of developing countries.